Screen design: a dynamic symmetry grid based approach - Ch'ng, E (2003)
This paper extends the study of dynamic symmetry as a screen layout technique. Research in the past was based on manually designed screens with minimal software support. This paper formulates the manual process into algorithms. Empirical results based on the study are presented. One study reformats user proposed layouts automatically while the other employs system grid interaction with users during design-time. Analysis of viewer selections yielded an average of 67.86 and 73.33% for those preferring dynamic symmetry screens over the originals. These experiments showed that incorporating dynamic symmetry into screen design tools can affect user's perception on interface aesthetics. (C) 2003 Elsevier B.V. All rights reserved.